Um olhar sobre o ensino de piano para adultos - Aline Maria Tomanik (2011)
As a piano teacher for over 10 years, I have observed that adults who are either professionally established or retired, and therefore do not intend to become professional musicians have been demonstrating a rising interest in acquiring musical abilities, especially in what concerns the study of instruments. The piano teachers who work with such students normally consolidated their pianistic training courses in the bachelor's degree in piano. However, such courses do not necessarily provide them with pedagogical courses directed to teaching piano to adults. This research proposes a reflection on issues related to the practice of teaching piano to adults. To develop this literature, bibliographic research related to piano pedagogy, piano teacher training, teaching/ learning and motivation was made. Using the bibliographic research as a starting point, we prepared questionnaires for teachers and piano students. The topics of these questionnaires generated the four chapters of this work, they being: (1) training, teaching experience and musical experience, (2) development of pianistic skills, (3) processes of teaching / learning, (4) motivation, attitudes and teacher-student relationship. This research was attended by four piano teachers and six of their students who agreed to answer the questionnaire. Their answers, together with the comments of the consulted authors, promoted reflections relevant to the practice of teaching piano to adults.